Learning for the Future: Exploring Effective Characteristics of Sustainability Leadership Programs in Higher Education - Hannah Allen (Canadian Society for Studies in Education, 2021)
In response to global environmental, economic, and social issues, universities and colleges have begun to create and expand leadership courses and programs that aspire to foster sustainability change agents. This literature review explores these courses and programs in greater detail and identifies the characteristics they share. In doing so, it maintains a common focus on education that is collaborative, experiential, and transformative while providing examples of effective pedagogies, skills, and learning outcomes that support these themes. This review contributes to emerging research on best practices for sustainability education and can potentially provide insights for sustainability educators, researchers, and students at the post-secondary level.